Seroprevalence of SARS COV-2 anti-nucleocapsid antibodies in Turkish healthcare workers before vaccination schedule: January 2021 - Ayşin Kılınç Toker; Ayşe Turunç Özdemir; Duygu Çerçioğlu Özdemir; Esma Eryilmaz Eren; Esma Saatçi; İbrahim Toker; İlhami Çelik (National Scientific Medical Center, 2022)
Objective: We aimed to assess the seroprevalence of SARS-CoV-2 infection and associated factors among Turkish HCWs, before the Covid-19 vaccination program in January 2021. Material and methods: We performed antibody assessment against SARS-CoV-2 in blood samples from participants using the Elecsys® Anti-SARS-CoV-2 electrochemiluminescence immunoassay. Samples with a cut-off index (COI; signal sample/cut-off) <1.0 were considered negative, samples with ≥1.0 were deemed positive. Results: 714 HCWs, 487 women (68.2%), were included in our study. The mean age of the participants was 35.9 ± 8.4 (min:18, max: 62). 370 (51.8%) HCWs's the antibody level was negative, and 344 (48.2%) was positive. While 47.1% (n=122) of the HCWs with positive RT-PCR were antibody positive, 48.8% (n=222) were negative. There was no statistically significant difference in mean age and age groups (p values ​​0.338 and 0.414, respectively). Also, there was no statistically significant difference in antibody levels by gender (p=0.236). There was no significant difference between antibody positivity according to the presence of comorbidity, and the risk area studied (p=0.556, p=0.335, respectively). There was a statistically significant difference between lung involvement and antibody positivity during Covid-19 infection (p= <0.001). Conclusion: In our study, the seroprevalence of SARS-CoV-2 antibodies in HCWs was higher than the average population and approximately fifty percent. Multicenter studies with more HCWs would be helpful to determine overall seroprevalence rates.